Implementation of the Literacy Movement on Student Learning Motivation in Elementary Schools - Soffanah Dina Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the literacy and numeracy abilities of elementary school students in increasing students' motivation and interest in reading and numeracy at the elementary level. The school literacy movement can strengthen the character movement as outlined in the Minister of Education and Culture Regulation Number 23 of 2015. One of the activities in the literacy movement is reading for approximately 15 minutes before teaching and learning activities begin. Numeracy is the ability to understand and apply numbers and arithmetic operations. This type of research method is a descriptive qualitative research using survey data and direct observation of elementary schools accompanied by sources from previous research. The results of this study indicate that with the existence of a school literacy movement that is carried out for 15 minutes it can train or familiarize students with increasing students' reading abilities and interest in teaching and learning activities at school